Coevolution of cooperation and epidemic spreading - Mehran Noori; Nahid Azimi-Tafreshi; Mohammad Salahshour (Physical Review Research)
People's cooperation in adopting protective measures is effective in epidemic control and creates herd immunity as a public good. Similarly, the presence of an epidemic is a driving factor for the formation and improvement of cooperation. Here, we study the coevolution of epidemic dynamics and the public goods game as a paradigm of cooperation dynamics. Using simulations and a mean-field description, we show that the interaction of the evolutionary dynamics of cooperation and epidemic spreading leads to a feedback loop between the two dynamics. The higher disease transmission rate can promote cooperation and lead to the reduction of disease spread; in turn, the higher benefit of cooperation leads to the more efficient control of epidemics. Additionally, our work shows that a higher altruistic effect of cooperation in controlling the disease can only be detrimental to the evolution of cooperation and disease control. Rather, individuals' choices in adopting costly preventive measures are predominantly driven by the self-interested effect of such measures in reducing the probability of getting infected.